2022
DOI: 10.1186/s12967-022-03679-y
|View full text |Cite
|
Sign up to set email alerts
|

CSPG4 expression in soft tissue sarcomas is associated with poor prognosis and low cytotoxic immune response

Abstract: Background Soft tissue sarcomas (STS) are heterogeneous and pro-metastatic tumors. Identification of accurate prognostic factors and novel therapeutic targets are crucial. CSPG4 is a cell surface proteoglycan with oncogenic functions. It recently emerged as a potential target for immunotherapy, including cell therapy based on CSPG4-specific chimeric antigen receptor (CAR)-redirected cytokine-induced killer lymphocytes (CSPG4-CAR.CIKs) in STS. However, expression of CSPG4 is poorly known in STS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…[31] CSPG4 functions as a cell surface proteoglycan and promotes oncogenesis. [32] In BLCA, elevated expression of CSPG4 indicates a poor prognosis. [33] Researchers have found that BLCA tissues that became resistant after treatment with cisplatin and gemcitabine showed a significant increase in CSPG4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…[31] CSPG4 functions as a cell surface proteoglycan and promotes oncogenesis. [32] In BLCA, elevated expression of CSPG4 indicates a poor prognosis. [33] Researchers have found that BLCA tissues that became resistant after treatment with cisplatin and gemcitabine showed a significant increase in CSPG4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…CSPG4 (Chondroitin Sulfate Proteoglycan 4), also known as NG2 or MCSP, is a transmembrane proteoglycan that is found on the outer layers of various cell types, including pericytes, glial cells, and melanoma cells. It is involved in cell adhesion, migration, and proliferation, as well as regulating the signaling pathways involved in these processes [ 27 ]. CSPG4 is a marker for pericytes, which are cells that play a role in maintaining the stability and function of blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Chondroitin sulfate proteoglycan 4 (CSPG4) has been demonstrated to exhibit aberrant expression in various tumor types, including soft tissue sarcoma, squamous cell carcinoma of the head and neck, breast cancer, and anaplastic thyroid cancer. Furthermore, CSPG4 has been shown to play a pivotal role in promoting tumor proliferation and metastasis [22][23][24]. Simultaneously, CSPG4 serves as a promising therapeutic target for cancer.…”
Section: Introductionmentioning
confidence: 99%